Entrepreneurial Competencies and Networks in the Construction Industry - Puteri Fadzline, Muhamad Tamyez; Nazaruddin, Ishak; Juhary, Ali; Safiynaz, Omar (ESB Business School, 2016)
The construction industry plays an important role in the economic growth and in the long-term national development. Although some studies have shown that the failure rate and bankruptcies among the construction firms are high. One of the critical issues facing the construction industry in Malaysia is to ensure that the industry can attain and able to sustain the anticipated growth. This research attempts to empirically examine the significance of the entrepreneurial competencies and entrepreneurial networks on entrepreneurial success of small size contractors in Malaysia. It adapts the quantitative approach and carried out in the state of Selangor where stratified random sampling was adapted. Questionnaires were conducted as means of collecting data. Based on the total number of population of G1 to G3, the sample size is 368 respondents. Quantitative research revealed that personal competency has the highest effect on the success of the construction firms (β=.231), and social network (β=.223). Hence, the study’s empirical findings provide a basis for recommendations for small size construction firms to enhance their competencies and for the policy makers to design and formulate entrepreneurship support programs and other initiative for SMEs especially the small size construction firms.